Penerapan Supervisi Klinis Sebagai Upaya Meningkatkan Kompetensi Pedagogik Guru Di SMP Negeri 30 Surabaya - Ahmad Syuhadak (Educational Research Center, 2025)
This School Action Research (SAR) was conducted at SMP Negeri 30 Surabaya to improve teachers' pedagogical competencies by implementing clinical-based classroom supervision. The research focused on assessing the impact of clinical supervision on the teachers' ability to develop and execute effective lesson plans and enhance their teaching practices. The study was carried out in two cycles, each involving stages of planning, action, observation, and reflection, to ensure systematic improvement. Data were collected through classroom observations, pre- and post-supervision interviews, and reflective discussions with teachers, school principals, and supervisors. The findings demonstrated a significant increase in the quality of lesson planning and teaching practices. Specifically, the assessment score for lesson planning rose by 27.9%, from an average of 3.4 in Cycle I to 4.4 in Cycle II, while the score for teaching implementation improved by 16.8%, from an average of 3.7 in Cycle I to 4.3 in Cycle II. These results underscore the effectiveness of clinical supervision in bridging the gap between current and ideal teaching practices, fostering a more reflective and responsive teaching approach. However, challenges were identified, including the varying readiness of teachers for clinical supervision and limited opportunities for regular supervision due to the administrative duties of school leaders and supervisors. To overcome these barriers, a more collaborative and well-coordinated approach is needed, along with efforts to build a positive mindset among teachers about the benefits of supervision. In conclusion, clinical supervision, when strategically implemented, serves as a powerful tool for enhancing teaching quality and promoting continuous professional development in schools..